Treatment of patella tendinopathy by distalising tibial tubercle osteotomy - Dan, Michael J (BMJ Case Rep, 2019)
Patella tendinopathy condition is often resistant to conservative treatment. We report a case of patella tendinopathy treated by distalisation of the tibial tubercle with excellent long-term result.